2021
DOI: 10.3390/ijms22116148
|View full text |Cite
|
Sign up to set email alerts
|

A New Ultrasensitive Bioluminescence-Based Method for Assaying Monoacylglycerol Lipase

Abstract: A novel bioluminescent Monoacylglycerol lipase (MAGL) substrate 6-O-arachidonoylluciferin, a D-luciferin derivative, was synthesized, physico-chemically characterized, and used as highly sensitive substrate for MAGL in an assay developed for this purpose. We present here a new method based on the enzymatic cleavage of arachidonic acid with luciferin release using human Monoacylglycerol lipase (hMAGL) followed by its reaction with a chimeric luciferase, PLG2, to produce bioluminescence. Enzymatic cleavage of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…The choice of this acyl chain derives from our previous studies [ 31 , 32 , 33 , 34 , 35 ], which have suggested medium-short chains as a versatile substrate of lipase and esterase activity evaluation, and it is also supported by the recent literature [ 18 ]. Indeed, in a rational design of a substrate for lipolytic activity evaluation, the alkyl chain length should be carefully evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of this acyl chain derives from our previous studies [ 31 , 32 , 33 , 34 , 35 ], which have suggested medium-short chains as a versatile substrate of lipase and esterase activity evaluation, and it is also supported by the recent literature [ 18 ]. Indeed, in a rational design of a substrate for lipolytic activity evaluation, the alkyl chain length should be carefully evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, continuing our interest in lipase selective probe development [ 31 , 32 , 33 , 34 , 35 ] suitable for in vitro and in vivo assays, we investigated a group of phenoxy-1,2-dioxetane luminophores, 2 – 4 , carrying an octanoyl chain as a triggerable substrate. The enzymatic cleavage of these phenoxy-dioxetane luminophores generates a direct chemiluminescence emission which is strongly dependent on the lipase activity.…”
Section: Introductionmentioning
confidence: 99%